Analisis Pendapatan Usahatani Jagung (Zea mays L.) pada Lahan Kering Desa Bakti Kecamatan Pulubala Kabupaten Gorontalo - Felmi Yunus; Zainal Abidin; Deyvie Xyzquolyna (Fakultas Pertanian Universitas Ichsan Gorontalo, 2018)
The research aimed to analyze the income of maize farming on dryland in Bakti Village, Pulubala district of Gorontalo Regency. The method used was survey and interview on maize farmers. The results showed that the farmers on dryland had increased revenue amount Rp 7.198.748/ ha.